Перспективи застосування системного підходу у соціальній роботі з дітьми з розладами аутичного спектру - Федорова, Вікторія Денисівна; Fedorova, Viktoriia Denysivna (Національний університет "Львівська політехніка", 2024)
Робота досліджує перспективи системного підходу у соціальній роботі з дітьми з розладами аутичного спектра (РАС) в Україні, що є актуальним з огляду на перехід від фрагментарної до комплексної підтримки. Важливою проблемою також залишається недостатнє впровадження міждисциплінарної співпраці. Об’єкт дослідження - соціальна робота з дітьми з розладами аутичного спектру на сучасному етапі в Україні. Мета дослідження - теоретичне та практичне обґрунтування перспектив застосування системного підходу в соціальній роботі з дітьми, які мають розлади аутичного спектру. Результати дослідження: У роботі проаналізовано системний підхід та його поєднання з міждисциплінарною співпрацею в соціальній роботі з дітьми з РАС, зокрема перехід до індивідуалізованих стратегій. Досліджено моделі соціальної підтримки в Україні та за кордоном, виявлено проблеми нормативного регулювання, кадрової спроможності та бар’єри впровадження системного підходу. Емпіричне дослідження на основі інтерв'ю з фахівцями Центру «Джерело» виявило ефективні практики, труднощі та надало рекомендації щодо впровадження гнучкої координаційної моделі підтримки.міждисциплінарна взаємодія.

The work explores the prospects for a systemic approach in social work with children with autism spectrum disorders (ASD) in Ukraine, which is relevant in view of the transition from fragmented to comprehensive support. An important problem also remains the insufficient implementation of interdisciplinary cooperation. Object of research: is social work with children with autism spectrum disorders at the present stage in Ukraine. Subject of the study: is the prospects for the application of a systemic approach in social work with children with autism spectrum disorders. Objective: is theoretical and practical justification of the prospects for the application of a systemic approach in social work with children with autism spectrum disorders. Research results: The paper analyzes the systemic approach and its combination with interdisciplinary cooperation in social work with children with ASD, in particular the transition to individualized strategies. Models of social support in Ukraine and abroad are studied, problems of regulatory regulation, personnel capacity and barriers to the implementation of a systemic approach are identified. Empirical research based on interviews with specialists of the Dzherelo Center revealed effective practices, difficulties and provided recommendations for the implementation of a flexible coordination model of support.
Prospects for applying a systems approach in social work with children with autism spectrum disorders
Keywords: 6.231.00.00; системний підхід; соціальна робота; діти з аутизмом; РАС; systemic approach; social work; children with autism; ASD; interdisciplinary interaction. List of used literature sources. 1. Bibikova; T. M. (2019). Autism as a social phenomenon: problems and prospects. Lviv: Svit Publishing House. 134. 2. Laevska N. (2018). The process of socialization. Primary school children with early childhood autism in modern society. Psychologist. 2018. No. 11/12. 64–77. 3. Stolyaryk; O.; Semigina; T. & Zubchik; O. (2020). Family social work: realities of Ukraine. Scientific Bulletin of the South Ukrainian National Pedagogical University named after K. D. Ushynsky; 4